STUDI ETNOGRAFI : KONSEP TRANSFROMASI GEOMETRI KERIS KYAI TENGARA - Annastiar, Sabrina; Chandra, Fabira; Muzaiyanah, Ufiq; Arfinanti, Nurul; Suparni, Suparni (JURNAL MathEdu (Mathematic Education Journal), 2025)
This research is motivated by the existence of a link between cultural elements that can represent mathematical objects as an alternative learning media in mathematics material. Indonesia has a variety of cultural heritages, one of which is Keris. This culture can be used to explore mathematical concepts to bring mathematics closer to cultural elements; it can also be used in the context of school learning. The main objective of this study is to examine the concept of geometric transformation contained in the Keris motif, the Keris, which is the main object in this study, namely "Keris Kyai Tengara". This research is included in qualitative research using an ethnographic approach. This study's data collection process was done through observation, documentation and interviews with Kris's caretakers and mathematicians. The results of this study indicate that the motifs in the kyai tengara kris apply the concept of geometry transformation. The idea of translation is found in the blue fan motif, the concept of reflection is found in the pattern of animal motifs on the kris frame, and the idea of dilation is found in the pattern of elephant wings on the kris.